(Micro)aggressions in everyday racism in Portugal: a quantitative analysis (Cadernos de Sociomuseologia, 2025)
This article reflects on the various manifestations of everyday racism in Portugal based on the categories of racial microaggressions, as conceived by Charles Peirce, developed by Derald Sue, and scaled according to the Racial Microaggression Scale (RAMS). It then analyzes the results of the Preliminary Diagnostic Survey “Everyday Racism in Portugal,” conducted as part of the AGRRIN - Gerando Corpos Project. From aggression to insurgency: contributions to a decolonial pedagogy (FCT 2022.06269.PTDC), which involved the participation of 140 black individuals, Afro-descendants, and/or individuals of African origin. In addition to presenting the variety of aggressions suffered by the interviewees, the research also reflects the potential for insurgencies against such behaviors.Keywords: Racism; Everyday racism; Microaggressions; Racism in Portugal